Determination of Particle Size Distribution of Used Black Tea Leaves by Scanning Electron Microscope - Hossain, Mohammad Abul; Mori, Shigeru (Dhaka University Journal of Science, 2013)
The particle size distribution (PSD) of a particulate material is important in understanding its physical and chemical properties. Determination of PSD is essential in many physicochemical processes and production quality depends on the measurement and control of PSD. Scanning electron microscope (SEM), in addition to sieve analysis, has been used to determine the PSD of biomass materials like used black tea leaves (UBTL). Spherical, ellipsoidal and non-spherical particles of used black tea leaves were observed in SEM images. The PSD of four different sizes ranges of spherical and non spherical UBTL particles was determined from the measurement of SEM images of length wise and width wise diameters. The results enabled to determine the mean diameter or representative diameters of particles of wide size ranges. Dhaka Univ. J. Sci. 61(1): 111-115, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15106